Rare bird documentation form for Bohemian Waxwing at Cherokee, 1982 - Bierman, Dicket al (1982)
Rare bird documentation form for a Boehmian Waxwing at Cherokee in Cherokee County, IA on March 12, 1982. Epson - sheet feed